2023
DOI: 10.3390/ijms24043980
|View full text |Cite
|
Sign up to set email alerts
|

Calpain Regulates Reactive Oxygen Species Production during Capacitation through the Activation of NOX2 and NOX4

Abstract: Capacitation is a series of physiological, biochemical, and metabolic changes experienced by mammalian spermatozoa. These changes enable them to fertilize eggs. The capacitation prepares the spermatozoa to undergo the acrosomal reaction and hyperactivated motility. Several mechanisms that regulate capacitation are known, although they have not been fully disclosed; among them, reactive oxygen species (ROS) play an essential role in the normal development of capacitation. NADPH oxidases (NOXs) are a family of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…Additionally, Pecchillo Cimmino et al detailed the effect of NADPH oxidase (NOX)-generated superoxide anion on various metabolic pathways, with particular reference to the NOX1-, NOX2-, and NOX4-induced reprogramming of the cancer cell metabolism [3]. Ortiz-García reported that NOX2 and NOX4 interact and form aggregates in the acrosome of mammalian spermatozoa [4]. The interaction is disrupted in the capacitated spermatozoa in a calpain-dependent manner.…”
mentioning
confidence: 99%
“…Additionally, Pecchillo Cimmino et al detailed the effect of NADPH oxidase (NOX)-generated superoxide anion on various metabolic pathways, with particular reference to the NOX1-, NOX2-, and NOX4-induced reprogramming of the cancer cell metabolism [3]. Ortiz-García reported that NOX2 and NOX4 interact and form aggregates in the acrosome of mammalian spermatozoa [4]. The interaction is disrupted in the capacitated spermatozoa in a calpain-dependent manner.…”
mentioning
confidence: 99%